Pengaruh Penggunaan Media Sosial Terhadap Perilaku Keagamaan Remaja di Jorong Parit Panjang Kecamatan Lubuk Basung Kabupaten Agam - Dona Ariswandi; Hidra Ariza (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by a change or decline in the religious behavior of teenagers in Jorong Parit Panjang, where many teenagers use social media excessively, which makes their religious behavior show a less than good attitude. Such as often neglecting to perform worship because they are too engrossed in using social media, as well as a lack of socialization in the community. In this research, the method used is a quantitative method with product moment correlation coefficient data analysis techniques using SPSS 25. Using data collection techniques through questionnaires. In this research, the sample used was 35 people. The results of this research show that there is an influence between the use of social media on the religious behavior of teenagers in Jorong Parit Panjang, Lubuk Basung District, Agam Regency with a correlation coefficient value of 0.760 in the interval 0.75-0.99. This means that the independent variable (Use of Social Media) has an influence on the dependent variable (Adolescent Religious Behavior), which means it has a very strong influence. Meanwhile, 0.05 or (5%) is influenced by other factors and the coefficient of determination is 0.760 or 76%. So based on the results of this research it can be concluded that there is a significant influence between the use of Social Media on the religious behavior of teenagers in Jorong Parit Panjang, Lubuk Basung District, Agam Regency.